2021
DOI: 10.1111/bjh.17382
|View full text |Cite
|
Sign up to set email alerts
|

Relative expansion of CD19‐negative very‐early normal B‐cell precursors in children with acute lymphoblastic leukaemia after CD19 targeting by blinatumomab and CAR‐T cell therapy: implications for flow cytometric detection of minimal residual disease

Abstract: CD19-directed treatment in B-cell precursor acute lymphoblastic leukaemia (BCP-ALL) frequently leads to the downmodulation of targeted antigens. As multicolour flow cytometry (MFC) application for minimal/measurable residual disease (MRD) assessment in BCP-ALL is based on B-cell compartment study, CD19 loss could hamper MFC-MRD monitoring after blinatumomab or chimeric antigen receptor T-cell (CAR-T) therapy. The use of other antigens (CD22, CD10, CD79a, etc.) as B-lineage gating markers allows the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 39 publications
4
63
2
1
Order By: Relevance
“…The model predicted relative proportions of B-cell subsets and CAR T subsets directly attainable from the flow cytometry data of long-term remission patients. In particular, the reorganization of the B-cell subsets, with a predominant CD19 − compartment, has recently been reported in patients who respond to anti-CD19 therapy [54]. This otherwise unnoticeable precursor could reach up to 100% of all the B-cell precursors, as shown here.…”
Section: Discussionsupporting
confidence: 72%
“…The model predicted relative proportions of B-cell subsets and CAR T subsets directly attainable from the flow cytometry data of long-term remission patients. In particular, the reorganization of the B-cell subsets, with a predominant CD19 − compartment, has recently been reported in patients who respond to anti-CD19 therapy [54]. This otherwise unnoticeable precursor could reach up to 100% of all the B-cell precursors, as shown here.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, the use of other early B‐line antigens [CD22, CD24, CD10, intracellular (i) CD79a] instead of CD19 for primary B‐cell gating, such as to improve the MFC‐MRD technique in the case of CD19‐targeted treatment, 7,10,11 could lead to errors in the interpretation of the immunophenotype of normal haematopoietic cells. Recently we have shown that after CD19 targeting in children with R/R BCP‐ALL by either blinatumomab or chimaeric antigen receptor (CAR)‐T cells, a relative expansion of normal very early CD19‐negative BCPs can be observed 12 . Due to the specific immunophenotype, which is very different from that of mature CD19‐positive BCPs, these normal cells could be misinterpreted during the MFC‐MRD assessment as developing a CD19‐negative relapse 12 .…”
Section: Figurementioning
confidence: 99%
“…Recently we have shown that after CD19 targeting in children with R/R BCP‐ALL by either blinatumomab or chimaeric antigen receptor (CAR)‐T cells, a relative expansion of normal very early CD19‐negative BCPs can be observed 12 . Due to the specific immunophenotype, which is very different from that of mature CD19‐positive BCPs, these normal cells could be misinterpreted during the MFC‐MRD assessment as developing a CD19‐negative relapse 12 . MRD studies are central to evaluating the effectiveness of targeted treatment 5,13 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations